Mutations in PCYT2 disrupt etherlipid biosynthesis and cause a complex hereditary spastic paraplegia - Vaz, Frédéric; McDermott, John H.; Alders, Mariëlle; Wortmann, Saskia Brigitte; Kölker, Stefan; Pras-Raves, Mia L.; Vervaart, Martin A. T.; van Lenthe, Henk; Luyf, Angela C. M.; Elfrink, Hyung L.; Metcalfe, Kay; Cuvertino, Sara; et al. (Brain, 2019)
Vaz, McDermott et al. identify variants in PCYT2, which encodes a key gene in phospholipid biosynthesis, in five individuals with a new complex hereditary spast